CURRENT EPIDEMIOLOGICAL TRENDS OF FIRST PERMANENT MOLAR PATHOLOGY DURING FIRST YEARS OF AGE 6-12 ASSESSED IN IASI AREA - Veronica Şerban; Adriana Balan; Maxim Adam (Romanian Dental Association for Education, 2014)
Dentistry research, in recent years showed a considerable increase in the frequency of first permanent molar damage. Purpose of study: Quantification and monitoring objective of the study by evaluating data from a representative group of children, aged 6-12 years, in order to determine the prevalence and incidence of first permanent molar pathology at Iasi area. Materials and methods: The study group consisted in a number of 804 young patients, diagnosed with a diverse complex diseases, among them 350 lived in rural and 454 urban areal of Iasi. The methodology consisted of clinical and laboratory evaluation of patients, according to WHO recommendations. Data records of personal transcript were centralized and database was processed statistically. Results and discussion: Prevalence of decays in permanent first molar increased significantly with age. It appears in this study group that: first permanent molars receive a high rate of decay; the prevalence index is 90%. Generally, the frequency of decay increases gradually with age. Comparatively to entire group of children, simple decay is found at 81.64% of cases and 18.35% of cases had complicated decays. Conclusions: Patients assessed presented first permanent molar frequently and early affected by caries. Between 6 -8 years: 25,8% lower molars have cavities comparatively with 15% of maxillary molars. Between 9-10 years, 54% lower molars are affected by decays comparatively with 37, 2% maxillary molars. Between 11-12 years 72% of lower molars and 54, 2% of maxillary molars presented decays.